(untitled) (BIOTIK: Jurnal Ilmiah Biologi Teknologi dan Kependidikan, 2021)
The aims of this study to determine the improvement of students’ critical thinking skills through the application of learning model the Problem Based Learning in Biology subjects in class X SMA Negeri 1 Kluet Tengah. The subjects in this study were students of class X SMA Negeri 1 Kluet Tengah, with total of 31 students, with focus of this research critical thinking skills ability in Biology subjects. The research design used was classroom action research, which was conducted in two cycles. Each cycle consists of four stages, namely: planning, implementing, observing, and reflecting. In the pre-cycle, the students ’critical thinking ability was 37.81% in the less critical category, since implementation of the first cycle the students’ critical thinking ability became 51.80% with the fairly critical category. In cycle II, the average achievement of students’ critical thinking skills has increased to 76.90% in the critical category. Thus the results of this study indicate that the application of learning model the Problem Based Learning can improve students’ critical thinking skills in Biology subjects in Class X SMA Negeri 1 Kluet Tengah.